Measurement of properties of B(s)(0)s -> mu(+)mu(-) decays and search for B-0 -> mu(+)mu(-) with the CMS experiment - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Bergauer,T; Brandstetter,J; Dragicevic,M; Eroe,J; Del,Valle AE; Flechl,M; Fruehwirth,R; Jeitler,M; et al. (The Journal of High Energy Physics, 2020)
Results are reported for the B0s→ μ+μ− branching fraction and effective lifetime and from a search for the decay B0→ μ+μ−. The analysis uses a data sample of proton-proton collisions accumulated by the CMS experiment in 2011, 2012, and 2016, with center-of-mass energies (integrated luminosities) of 7 TeV (5 fb−1), 8 TeV (20 fb−1), and 13 TeV (36 fb−1). The branching fractions are determined by measuring event yields relative to B+→ J/ψK+ decays (with J/ψ → μ+μ−), which results in the reduction of many of the systematic uncertainties. The decay B0s→ μ+μ− is observed with a significance of 5.6 standard deviations. The branching fraction is measured to be B(B0s→μ+μ−)=[2.9±0.7(exp)±0.2(frag)]×10−9, where the first uncertainty combines the experimental statistical and systematic contributions, and the second is due to the uncertainty in the ratio of the B0s and the B+ fragmentation functions. No significant excess is observed for the decay B0→ μ+μ−, and an upper limit of (B0 → μ+μ−) < 3.6 × 10−10 is obtained at 95% confidence level. The B0s→ μ+μ− effective lifetime is measured to be τμ+μ−=1.70+0.61−0.44 ps. These results are consistent with standard model predictions.